Methodological Approaches to the Assessment of Historical and Cultural Resources in Tourist Destinations - FEDULIN, Aleksandr Alekseevich; ZGONNIK, Lyudmila Vladimirovna; LEBEDEVA, Olga Yevgenievna; DUKHOVNAYA, Liliya Leonidovna; ILKEVICH, Sergey Viktorovich (Journal of Environmental Management and Tourism; Vol 8 No 6 (2017): JEMT Volum VIII Issue 6(22) Fall 2017, 2018)
The article is devoted to the development of methodological approaches to the assessment of historical and cultural resources. It has been established that historical and cultural resources are not sufficiently used in the studied region. The developed methodology for the assessment of historical and cultural resources can be applied by state authorities in assessing the quality of historical and cultural resources in controlled entities. It has been proved that in each specific case the structure of the organization of the use of historical and cultural resources can be determined by the management based on the specifics of the activity. For the development of the historical and cultural potential, it was proposed to implement measures on restoration and reconstruction of historical and cultural heritage objects, develop an advertising campaign to promote historical and cultural objects, organize a network of tourist information centers, implement programs on personnel training, support promising applied research in the tourism and hospitality industry in the studied region.